Debussy's Resonance - Huebner, Steven; Medicis, François de, 1964- (Book collections on Project MUSE., 2018)
The music of Claude Debussy has always been widely beloved by listeners and performers alike, more perhaps than that of any of the other pioneers of musical modernism. However rich in itself, his creative output also participated, and continues to participate, in a network of cultural connections, the scope and meaning of which can only be gleaned through multiple interpretive frameworks. Debussy's Resonance offers twenty new studies by some of the most active and respected English- and French-language scholars of French music. The book treats a large swath of the composer's music, from previously unexplored melodies of his early years to late pieces such as the ballet Jeux and the Douze Etudes, and takes into consideration the numerous contexts that helped shape the works and the different ways that musicologists and critics have explained them.